2017
DOI: 10.1093/nar/gkx004
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between the polymerase and RNase H activity of HIV-1 reverse transcriptase

Abstract: Replication of human immunodeficiency virus 1 (HIV-1) involves conversion of its single-stranded RNA genome to double-stranded DNA, which is integrated into the genome of the host. This conversion is catalyzed by reverse transcriptase (RT), which possesses DNA polymerase and RNase H domains. The available crystal structures suggest that at any given time the RNA/DNA substrate interacts with only one active site of the two domains of HIV-1 RT. Unknown is whether a simultaneous interaction of the substrate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 44 publications
1
43
0
Order By: Relevance
“…Figiel et al have demonstrated that, under conditions where the DNA polymerase active site of HIV-1 RT is covalently liked to its substrate, nucleic acid can be simultaneously accessed by the RNA polymerase and RNase H active centers, indicating an important degree of coordination between its synthetic and hydrolytic activities [ 24 ]. Using this precedent, we speculated that ligand binding at the HBV RNase H domain might allosterically modulate P protein DNA polymerase activity, since we and others have demonstrated that α-HTs inhibit HBV RNase H activity in vitro, and virus replication in culture [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figiel et al have demonstrated that, under conditions where the DNA polymerase active site of HIV-1 RT is covalently liked to its substrate, nucleic acid can be simultaneously accessed by the RNA polymerase and RNase H active centers, indicating an important degree of coordination between its synthetic and hydrolytic activities [ 24 ]. Using this precedent, we speculated that ligand binding at the HBV RNase H domain might allosterically modulate P protein DNA polymerase activity, since we and others have demonstrated that α-HTs inhibit HBV RNase H activity in vitro, and virus replication in culture [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whether DNA synthesis and RNA degradation can occur simultaneously has been a topic of debate (20,21). It is well established that DNA synthesis occurs more frequently and at a much faster rate than RNA hydrolysis during reverse transcription (22).…”
Section: Resultsmentioning
confidence: 99%
“…4). This may explain why RNA is still hydrolyzed by RNase H when the DNA end is cross-linked to the thumb or polymerase active site (21).…”
Section: Discussionmentioning
confidence: 99%
“…Our R7 substrate is sufficiently long to simultaneously bind both the HIV-1 polymerase and RNase H domains and is efficiently cleaved in our experiments, indicating that the constant dsDNA part of the R7 substrate binds the polymerase domain, even though a RNA–DNA heteroduplex have been shown to bind with higher affinity to the polymerase domain than dsDNA ( 53 ). Possibly, the preference for G or C in positions −2, −4 and −5 may be related to the requirement of substrate untwisting in order to reach the RNase H active site while simultaneously binding the polymerase domain ( 54 , 55 ).…”
Section: Discussionmentioning
confidence: 99%